2000
DOI: 10.1055/s-2000-9423
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Outcome in Growth-Restricted Versus Appropriately Grown Preterm Infants

Abstract: The objective of this paper is to examine whether growth-restricted preterm infants have a different neonatal outcome than appropriately grown preterm infants. All consecutive, singleton preterm deliveries between 27-35 weeks' gestation were included over a 4-year period. Infants with congenital anomalies and infants of diabetic mothers were excluded. Infants were categorized as small-for-gestational-age (SGA) when birth weight was at or below the 10th percentile, and appropriate-for-gestational-age (AGA) when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
5
18

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 13 publications
8
88
5
18
Order By: Relevance
“…Infants who are SGA have been found to be at decreased risk for EONS (454) but at higher risk for LONS than their appropriately grown gestational age-matched peers (82,437). This may be because SGA infants are susceptible to neutropenia associated with maternal preeclampsia or because they may require central venous catheters and parenteral nutrition for long periods due to a predisposition to feeding intolerance and NEC.…”
Section: Susceptibility Of Very-low-birth-weight Infants To Infectionmentioning
confidence: 96%
“…Infants who are SGA have been found to be at decreased risk for EONS (454) but at higher risk for LONS than their appropriately grown gestational age-matched peers (82,437). This may be because SGA infants are susceptible to neutropenia associated with maternal preeclampsia or because they may require central venous catheters and parenteral nutrition for long periods due to a predisposition to feeding intolerance and NEC.…”
Section: Susceptibility Of Very-low-birth-weight Infants To Infectionmentioning
confidence: 96%
“…24 Higher mortality rates are reported in those fetuses with absent or reversed end-diastolic flow on antenatal doppler velocimetry which is similar with present result. 25,26 In this study it was found that still birth and IUD (Intrauterine death) was 4(8%) and neonatal death was 3(6%).…”
Section: Resultmentioning
confidence: 93%
“…Both animal and human data suggest that IUGR increases the risk of sepsis and death from Gramnegative bacterial infections during the neonatal period (Simchen et al 2000). Lipopolysaccharide (LPS) is the main component of Gram-negative bacterial cell wall and is a potent inducer of the innate immune responses (Wenzel et al 1996, Rietschel et al 1996 through TLR4 (Poltorak et al 1998, Hoshino et al 1999.…”
Section: Intrauterine Growth Restriction Down-regulates Hepatic Tlr4 mentioning
confidence: 99%
“…Adverse factors that impair fetal growth such as maternal malnutrition, hinder immunological maturation as well (Moscatelli et al 1976, Chandra 1975a,b 1981, Ferguson 1978, Hasselbalch et al 1999. Both animal and human data suggest that those who are small for gestation show persistent immunological impairment for several months or even years (Chandra 1975c, Beach et al 1982, and that they are at increased risk of infections with Gram-negative bacteria during the neonatal period and childhood (Simchen et al 2000).…”
Section: Introductionmentioning
confidence: 99%